Reconstruction : the rebuilding of the United States after the Civil War - Cummings, Judy Dodge (Inquire and investigate., 2021)
Describes the history of the Reconstruction era after the Civil War, the challenges lawmakers faced, how the country was rebuilt, and how decisions made then affect the United States today. Includes text-related and discussion questions, activities, and research projects.